A retrospective controlled study of thiol disulfide homeostasis as a novel marker in Crimean Congo hemorrhagic fever. (2nd November 2017) - Tufan, Zeliha Kocak; Hasanoglu, Imran; Kolgelier, Servet; Alisik, Murat; Ergin, Merve; Yilmaz, Gul Ruhsar; Tasyaran, Mehmet A.; Erel, Ozcan; Guner, Rahmet
Abstract : Objectives: Crimean Congo hemorrhagic fever (CCHF) is the second most common hemorrhagic fever worldwide. This study aimed to evaluate the oxidant–antioxidant balance of patients with CCHF by detecting dynamic thiol disulfide homeostasis (TDH), which is a novel oxidative stress marker, and other molecules, including paraoxonase (PON), arylesterase (ARES), ceruloplasmin (CLP), myeloperoxidase (MPO), and catalase. Methods: This retrospective, cross-sectional, controlled study, which involved patients with CCHF and healthy volunteers, measured dynamic TDH using a novel automated method developed by Erel. Results: We recruited 69 adult patients with CCHF (31 females, 38 males, median age 46 years). The case fatality rate was 1.49% (1/69). Increased disulfide/native thiol and disulfide/total thiol ratios, decreased total antioxidant status (TAS), and increased total oxidant status (TOS) were found in patients with CCHF. TAS, PON, and ARES values were found to be positively correlated with both native and total thiol levels, whereas TOS and CLP were negatively correlated with both, at a significant level. MPO activity was similar in both groups. Discussion: This is the first study in the literature to evaluate dynamic TDH in CCHF. TDH shifts to the oxidative side in patients with CCHF, leading to an increase in TOS.